(untitled) (GYMNASIUM, 2021)
The objective of the research: is to ascertain and show the importance of the psychological influence on the juniors in the football game. The materials and methods used in the experiment were: motor tests: "30m straight line sprint", "Arrowhead Agility Drill" made with ball and without ball, with which we determine the motor level of the subjects and the psychological questionnaire DASS (Depression, Anxiety and Stress), with which we evaluate the negative emotional states in the sphere of depression, anxiety and stress; The motor tests recordings were made using the "Microgate Witty System" equipment. Conclusions: The motor results obtained from the tests are influenced by the psychological level of the athletes. Depression, stress, anxiety, having an important role in reaching the potential of the athletes, their level influencing the sports performance, fact demonstrated in our study.